Degradation of Benzene, Toluene, Ethylbenzene, and Xylene by Isolated Microorganisms from Petronas Gas Plant at Kertih, Terengganu - Salsali, Hamid Reza (1999)
A total of 38 isolates originating from five different sources of sediments, and contaminated soils from Petronas Gas Plant at Kertih, Terengganu were obtained through enrichment culture method using 0.1%(v/v) of benzene, toluene, ethylbenzene, and xylene or mixture of them as their sole energy and carbon sources. Most of the isolates were from S5 (Residential area) and the least from Sl(Equalization basin). Out of this, 11 good isolates were able to grow in varying hydrocarbon concentration up to 50% (v/v) BTEX. Only isolate No.4 showed extremely good growth in concentration up to 80% (v/v) of BTEX. Using benzene at 60% (v/v), the growth rate was observed to be highest during the first 2 hours, while degradation rate and percentage of removal by using isolate No.4 showed 1 .5E-04 mMis and 75% respectively. For toluene at 60% (v/v), the growth rate was highest during the first 3 hours, while degradation rate and percentage of removal were SE-OS rnMIs and 70% respectively. In the case ethylbenzene at 60% (v/v) , the growth rate was highest during the first 7hours, while degradation rate and percentage of removal by using same isolate showed lE-04 rnMIs and 98% respectively. For xylene at 60%(v/v), the growth rate was highest during the first 5hours, while degradation rate and percentage of removal achieved were 5.35E-04 rnMIs and 8.9% respectively. In general, all the isolates had tolerated the organic solvent (BTEX), which may be due to the adaptability of the cell membrane through a metabolic or enzymatic properties. Both High- Performance Liquid Chromatography and Gas Chromatography Mass-Spectra profile had clearly showed a BTEX-peaks area ratio reduction, where the isolates were shown to biodegrade the hydrocarbon either by mineralization or biotransformation. However, based on the almost complete peak reduction as well as appearance of unidentified peaks, it may be suggested that BTEX can be degraded by naturally present microorganisms which was identified at Petronas Gas Berhad site.